A produção de uma história local: concepções de história e memória na obra de Celestino Alves - Dantas, Fabiana Alves (2021)
The dissertation presented here is situated in the debate about the acting of dilettantes historians in the production of historical knowledge, especially in the context of local history. Its problem consists in analyzing the conceptions of history and memory present in Retoques da História de Currais Novos (1985), Vaqueiros e Vaquejadas (1986) and Matutos e Tropeiros (1989), productions by the writer Celestino Alves (Currais Novos/RN, april 06, 1929 – december 10, 1991), which deal with the municipality of Currais Novos and the region of Seridó potiguar. In theoretical-methodological terms, based on Michel de Certeau's (1995) concept of historical operation, the author's social place is investigated, his appropriation of sources and methodological operations, in addition to the discursive elaboration of the productions. The research allowed us to identify a historical operation in which the writing of local history is used to rid “traditional” aspects of oblivion in the face of the transformations triggered by modernization, aiming to form identity and social bond from the remembrance of what would be typical of the region, based, inclusively, on notions widespread throughout the 20th century about the Northeast and the Sertão. Thus, the identified conceptions consist of an understanding that history and memory are inseparable and, operating them together, the author uses them to fight forgetting. Therefore, the main conclusions of this work lead to reflections on the importance of studying the works of dilettantes historians and the relationships between history and memory existing in them, as well as on the existing demand in historiography regarding the production of local histories that contribute to a critical and reflective citizen formation.